How to teach English literature : overcoming cultural poverty - Webb, Jennifer (English teacher); Thom, Jamie (Melton, Woodbridge : John Catt Educational Ltd, 2019)
A practical guide to pedagogy in the English classroom, supporting the teaching abstract, classic and challenging texts and concepts.
Intro -- About the author -- Acknowledgements -- Foreword by Jamie Thom -- Introduction -- Section 1: Planning, Organisation and Working Practices -- Chapter 1: For Department Leaders: Creating the Right Conditions -- Chapter 2: Marking and Feedback Strategies -- Chapter 3: Planning and Preparation (how to teach really long books) -- Section 2: Reading and Analysis -- Chapter 1: Challenge and Aspiration -- Chapter 2: Language, Structure and Form -- Chapter 3: Context and Authorial Intent -- Chapter 4: Theory, Reception and Abstract Concepts -- Chapter 5: Prose -- Chapter 6: Poetry -- Chapter 7: Drama -- Chapter 8: Symbolism -- Section 3: Writing -- Chapter 1: Write Like a Literary Critic -- Chapter 2: Vocabulary -- Chapter 3: Sentence Level -- Chapter 4: Planning and Essay Structure -- Section 4: Memory, Recall, Revision and Homework -- Chapter 1: The Aim of the Game -- Chapter 2: Creating the Right Conditions for Learning -- Chapter 3: The Importance of Struggle -- Chapter 4: Activities and Teaching Strategies -- Section 5: Practical Walkthrough -- Section 6: Solutions.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: English literature -- Study and teaching (Secondary); English language -- Study and teaching (Secondary); English language -- Study and teaching (Secondary); English literature -- Study and teaching (Secondary)